Increased cognitive problem reporting after information about chemotherapy-induced cognitive decline: The moderating role of stigma consciousness. Issue 1 (2nd January 2017) - Jacobs, W.; Das, E.; Schagen, S.B.
Abstract : Objective: Information about treatment side effects can increase their occurrence; breast cancer (BC) patients showed increased cognitive problem reporting (CPR) and decreased memory performance after information about cognitive side effects. The current study extends previous research on adverse information effects (AIE) by investigating (a) risk factors, (b) underlying mechanisms and (c) an intervention to reduce AIE. Design: In an online experiment, 175 female BC patients were randomly assigned to one of three conditions. In the two experimental groups, patients were informed about the possible occurrence of cognitive problems after chemotherapy with (intervention group) or without (experimental group) reassuring information that 'there are still patients who score well on memory tests'. In the control group, no reference to chemotherapy-related cognitive problems was made. Main outcome measures: Main dependent measure was CPR. Four moderating and five mediating processes were examined. Results: CPR increased with higher levels of stigma consciousness in the two experimental groups, but not in the no-information control group. Conclusion: Merely informing patients about cognitive side effects may increase their occurrence, especially among individuals vulnerable to patient stereotypes. Adding reassuring information is not sufficient to reduce AIE.